Structural and magnetic characterization of electro-crystallized magnetite nanoparticles under constant current. (October 2015) - Mosivand, Saba; Kazeminezhad, Iraj
Graphical abstract: Structural and magnetic properties of electro-crystallized magnetite nanoparticles under constant current were studied. All samples were characterized using XRD, SEM, VSM, and Mössbauer spectrometry. Highlights: The effect of applied current on morphology and properties of Fe3 O4 is studied. The particle size and morphology are controllable by adjusting the current. The magnetization depends on particle size, type of surfactant and applied current. The clear correlation between magnetization and the mean particle size is observed. Abstract: The effect of applied current on the morphology, particle size, structure, and magnetic properties of magnetite nanoparticles prepared by electro-crystallization method was studied. The synthesis was performed in an electrochemical cell containing two iron electrodes and an aqueous solution of sodium sulfate, and either thiourea, sodium butanoate, or β-cyclodextrine as organic stabilizer. All the samples were characterized by XRD, SEM, VSM, and Mössbauer spectroscopy. X-ray diffraction patterns, clearly confirmed that all products have the cubic spinel Fe3 O4 crystal structure. Electron microscope images of the samples showed that their mean particle size is in the range 20–80 nm, and depends critically on the applied current and type of the organic additives. Specific magnetization of the samples at room temperature ranges from 60 to 90 A m 2  kg −1, depending on the growth conditions. Room temperature Mössbauer spectra are typical of nonstoichiometric Fe3− δ O4, with a small excess of Fe 3+, 0.06 ≤  δ  ≤ 0.17.